2002
DOI: 10.1159/000063108
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Removal of Therapeutic Drugs with a Novel Adsorbent System

Abstract: Background/Aim: Substances in the middle molecular weight range have been shown to play a significant pathogenetic role in as diverse disorders as end-stage renal disease and multiple organ failure. To overcome the limitations in the amount removed by hemofilters, new sorbents with a high biocompatibility are actively being developed. Furthermore, biocompatible sorbents by their nonspecific adsorptive behavior could have great impact on detoxification treatment in exogenous intoxications. We performed an in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
70
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 11 publications
5
70
0
Order By: Relevance
“…Drugs with >80% removal in an in vitro model after 120 min include vancomycin, teicoplanin, digoxin, tacrolimus, valproate, phenobarbital, carbamazepine and phenytoin and 60% removal of cyclosporine. 34 The Cytosorb column currently costs approximately £1000 although this will reflect commercial usage. It is not currently included in UK critical care commissioning agreements.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs with >80% removal in an in vitro model after 120 min include vancomycin, teicoplanin, digoxin, tacrolimus, valproate, phenobarbital, carbamazepine and phenytoin and 60% removal of cyclosporine. 34 The Cytosorb column currently costs approximately £1000 although this will reflect commercial usage. It is not currently included in UK critical care commissioning agreements.…”
Section: Discussionmentioning
confidence: 99%
“…These small-scale affinity chromatography experiments have demonstrated that an immunoadsorbent can remove b 2 -m from human plasma with an affinity that has not been achieved with hydrophobic interaction-based adsorbents [6,7]. Furthermore, these antibody-based adsorbents were found to be highly specific for b 2 -m, while the specificity of hydrophobic interaction-based adsorbents continues to be a concern [8,10]. To date, perhaps the most promising antib 2 -m immunoadsorbent has been reported by Vallar et al [41], which consisted of monoclonal antibodies immobilized onto Sepharose CL-4B gel beads.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, adsorbent matrices that are based on hydrophobic interaction and size exclusion (Lixelle ; Kaneka Co., Ltd., Tokyo, Japan and Betasorb ; Renaltech International LLC, New York, NY, USA) have been developed for the extracorporeal removal of b 2 -m [6,7]. However, their specificity and/or affinity for b 2 -m remains in question, complicating the evaluation of patient outcome due to their use [8][9][10].The ideal technology for the extracorporeal removal of b 2 -m should be highly specific, so as to prevent the significant loss of proteins and other molecules that are beneficial to the patient. A highly specific b 2 -m removal system could also serve as a valuable tool for research.…”
mentioning
confidence: 99%
“…10 Long-term HVHF increases the risk of drug and antibiotic extraction. 11 Moreover, long-term HVHF makes patient care more difficult and complicates common procedures, such as surgery or radiology. Finally and most importantly, longer treatments imply increased treatment costs, which may lead to decreased accessibility within the population, in particular of low-income countries.…”
mentioning
confidence: 99%